2002
DOI: 10.1089/109662002763003375
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Whey Protein Concentrate on the Inhibition of Stomach Ulcerative Lesions Caused by Ethanol Ingestion

Abstract: Objetivo Avaliar a atividade do hidrolisado das proteínas de soro de leite bovino e uma fração de peptídeos de baixo peso molecular (peso molecular ≤1kDa), na proteção do epitélio da mucosa do estômago de ratos Wistar adultos contra o processo ulcerativo, induzidos por três diferentes agentes. Métodos Nesse estudo foram utilizados os modelos de indução de úlcera pelo antiinflamatório indometacina (30mg/kg de peso), por etanol absoluto (1ml/animal) e por estresse causado por imobilização e frio (4 o C/2h) em ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…Lab.aLa, Comm.a-La, a pancreatin hydrolysate ($20% DH) of Comm.a-La and two hydrolysate fractions, F 1 (o1 kDa) and F 2 (41 kDa), decreased the ULI in the range of 32.2-49.8% as compared with the control, without statistical differences (p40.05) among them while the drug carbenoxolone lowered the ULI by 91%. It has been verified (Rosaneli et al, 2002) that the administration of two consecutive daily doses of 1000 mg kg À1 bw WPC reduced the ULI caused by 1 mL absolute ethanol by 73% while carbenoxolone (200 mg kg À1 bw) reduced it by 86.5%, based on physiological saline as the control.…”
Section: Article In Pressmentioning
confidence: 89%
See 2 more Smart Citations
“…Lab.aLa, Comm.a-La, a pancreatin hydrolysate ($20% DH) of Comm.a-La and two hydrolysate fractions, F 1 (o1 kDa) and F 2 (41 kDa), decreased the ULI in the range of 32.2-49.8% as compared with the control, without statistical differences (p40.05) among them while the drug carbenoxolone lowered the ULI by 91%. It has been verified (Rosaneli et al, 2002) that the administration of two consecutive daily doses of 1000 mg kg À1 bw WPC reduced the ULI caused by 1 mL absolute ethanol by 73% while carbenoxolone (200 mg kg À1 bw) reduced it by 86.5%, based on physiological saline as the control.…”
Section: Article In Pressmentioning
confidence: 89%
“…Studies reported recently (Rosaneli, Bighetti, Antoˆnio, Carvalho, & Sgarbieri, 2002, 2004) with a WPC produced in a pilot plant (Zinsly et al, 2001) and with a Comm.a-La (Matsumoto et al, 2001) demonstrated that whey proteins were capable of inhibiting the development of ulcerative lesions in the rat stomach mucosa by various ulcerogenic agents. Rosaneli et al (2004) used the same WPC, which was used in the present work to isolate a-La, and reported a 50% decrease of the ULI when two consecutive daily doses of 1000 mg kg À1 bw were administered to the rat, in the indomethacin model.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In a research by Rosaneli et al [51], it was observed that when rats showed a 41% reduction in ulcerative lesions caused by ethanol ingestion when they were fed a whey protein concentrate, while a 73% reduction rate was observed following repeat doses of whey (McGregor and Poppitt, 2013 [52]). …”
Section: Gastrointestinal Healthmentioning
confidence: 99%
“…This effect is thought to be related to the sulfhydryl component, particularly cysteine and its link with glutamic acid in the production of glutathione. In a study by Rosaneli et al (2002), rats fed a whey protein concentrate showed a 41% reduction in ulcerative lesions caused by ethanol ingestion while, a 73% reduction rate was observed following repeat doses of whey (Marshall, 2004;McGregor and Poppitt, 2013).…”
Section: Cardiovascular Disease Preventionmentioning
confidence: 99%